2018
DOI: 10.11604/pamj.2018.30.202.15966
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcomes of paediatric medical admissions at the Living Word Mission Hospital, Aba, South East Nigeria

Abstract: IntroductionThere is a decline in child mortality rate globally, courtesy of the erstwhile Millennium Development Goals. However, under-five mortality is still high in the African sub-regions. The need to review the morbidity and mortality pattern among children admitted into private health settings, where 60% of the medical conditions of the masses are being attended to in the sub-regions, cannot be overemphasized. This study aimed at documenting the morbidity pattern and outcomes of admissions among children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
3
8
1
Order By: Relevance
“…In the current study, visceral leishmaniasis, malnutrition, severe malaria and sickle cell disease were the most common causes of admission. Previous studies have shown that severe anemia, sickle cell disease, malaria and visceral leishmaniasis were the main causes of pediatric morbidity and mortality in eastern Sudan ( 17 , 18 ) and in other African countries, e.g., Nigeria, Tanzania, and Uganda ( 3 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, visceral leishmaniasis, malnutrition, severe malaria and sickle cell disease were the most common causes of admission. Previous studies have shown that severe anemia, sickle cell disease, malaria and visceral leishmaniasis were the main causes of pediatric morbidity and mortality in eastern Sudan ( 17 , 18 ) and in other African countries, e.g., Nigeria, Tanzania, and Uganda ( 3 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 740 medical files of children was calculated based on the reported rate of death (5.6%) in a previous study in Nigeria of children admitted to hospital ( 3 ). We assumed that 55 vs. 35% and 85 vs. 65% were the rates of the females and under-fives in children who died and children who survived, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be from the high proportion of patients receiving the correct empirical antibiotic treatment upon admission. The mortality in pediatric patients with suspected bloodstream infections in Anka is higher than the average pediatric mortality reported from secondary hospitals in Nigeria in Aba (5.7%) 18 and Asaba (5.8%) 19 . It is also higher than the overall average monthly pediatric hospital mortality from AGH (8.3%, MSF unpublished data).…”
Section: Discussionmentioning
confidence: 64%
“…This finding is surprising and could be explained by the fact that several conditions including infections can elicit increased CRP levels [21]. To be noted, infections as malaria are a common cause of hyperthermia [22] [23] [24].…”
Section:  Population Distribution By Origin and Residencementioning
confidence: 99%